DESKRIPSI KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DALAM PEMBELAJARAN MATEMATIKA NALARIA REALISTIK - Eric Dwi Putra (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2019)
This study aims to describe students' mathematical communication skills in the process of mathematics nalaria realistic learning. The approach used in this study is a qualitative approach because in this study will describe mathematical communication skills in realistic mathematical learning. Methods of data collection using tests and interviews. Data analysis techniques in this study are validity of instrument and time triangulation. The subjects in this study were gifted students of class VIII of Al Furqan Jember Middle School, which numbered 3 students and were taken by each student from high, medium and low ability. The results showed that for groups of students who had high abilities were able to fulfill all indicators of the mathematical communication abbility, while for students in the categorized group, just able to meet 4 indicators from 5 indicators for mathematical communication skills, and none for students with low ability categories. able to have for mathematical communication indicators in mathematics nalaria realistic learning.